Clinical, biochemical and molecular phenotype of congenital disorders of glycosylation: long-term follow-up - Bogdańska, Anna (Orphanet J Rare Dis, 2021)
BACKGROUND: Congenital disorders of glycosylation (CDG) result from defects in the synthesis of glycans and the attachment of glycans to proteins and lipids. Our study aimed to describe the clinical, biochemical, and molecular findings of CDG patients, and to present the long-term follow-up. MATERIAL AND METHODS: A single-center study (1995–2019 years) of patients with congenital disorders of N-glycosylation and combined N- and O-hypoglycosylation was performed. RESULTS: Among 32 patients included into the study, there were 12 PMM2-CDG, 3 ALG13-CDG, 3 ALG1-CDG, 1 ALG3-CDG, 3 MPI-CDG, 1 PGM1-CDG, 4 SRD5A3-CDG, 1 DPAGT1-CDG, 3 ATP6AP1-CDG, 1 ATP6V0A2-CDG. The phenotypic and genotypic spectrum during long-term (in some cases over 20 years) observation was characterised and several measurements of serum Tf isoforms taken. Statistical analysis revealed strong negative correlation between asialo-Tf and tetrasialo-Tf, as well as between disialo-Tf and tetrasialo-Tf. Within CDG type I, no difference in % Tf isoforms was revealed between PMM2-CDG and non-PMM2-CDG patients. However, these two groups differed significantly in such diagnostic features as: cerebellar ataxia, failure to thrive, hypothyroidism, pericardial effusion, cardiomyopathy, inverted nipples, prolonged INR. The effect of treatment with mannose in 2 patients with MPI-CDG was assessed and we found that % of asialo-Tf, monosialo-Tf, and disialo-Tf was significantly lowered, whereas tetrasialo-Tf and pentasialo-Tf rose, coming closer or falling into the reference range. CONCLUSIONS: The novel finding was an abnormal Tf IEF pattern in two ALG13-CDG patients and normal in one ALG1-CDG patient. Clinical manifestation of presented CDG patients was similar to that reported in the literature. Mannose supplementation in MPI-CDG patients, as well as galactose supplementation in PGM1-CDG patient, improved patients’ clinical picture and Tf isoform profiles.